ANALYSIS OF THE USE OF JIG TACK WELDING BRACKET RUBBER PAD TO IMPROVE THE ACCURACY OF THE WELDING PROCESS - Junaidi, Ahmad; Sona, Yoda Arya; Hendradinata (Politeknik Negeri Sriwijaya, Indonesia, 2026)
The primary issue in the assembly process of bracket rubber pads is dimensional deviation caused by the manual tack welding process. This study aims to evaluate the effectiveness of using a JIG as a fixture to improve the accuracy of tack welding. The research was conducted experimentally by applying a specially designed JIG to hold components firmly in place during the welding process. Dimensional measurements of assemblies produced with and without the JIG were compared and analyzed using the simple linear regression method. The results indicate that the use of a JIG significantly reduces dimensional deviations, resulting in more stable and accurate dimensions within standard tolerances. Therefore, the application of a tack welding JIG is proven effective in enhancing welding accuracy and is recommended for mass production purposes.